Editor's Introduction - Asad Zaman (International Econometric Review (IER), 2009)
Welcome to this first issue of International Econometrics Review. We aim to make this journal unique in many different ways, and hope to fill the many gaps between real world applications and theoretical econometrics that continue to exist and widen. Of course, achieving high goals depends on readers and contributors and we encourage the participation of all in this project.
Keywords: 330